CIRCULAR ECONOMY: CHALLENGES AND OPPORTUNITIES IN THE CONSTRUCTION SECTOR OF KAZAKHSTAN - Torgautov, Beibut; Zhanabayev, Asset; Tleuken, Aidana; Turkyilmaz, Ali; Mustafa, Mohammad; Karaca, Ferhat (Buildings, 2021)
The circular economy in the construction sector in emerging economies is one of the most promising concepts that aims to keep the value of the construction materials and structures as long as possible. The construction industry is rapidly developing in Kazakhstan with a yearly increase in projects. This research paper investigates the construction sector in Kazakhstan in terms of the potential application of circular economy principles by local stakeholders—clients, contractors, designers, and manufacturers. As limited research has been conducted on the circularity within the construction environment, including construction parties, this paper aims to fill this research gap. It seeks to identify the construction trends and perform a barrier and opportunity analysis to develop circular economy principles in the construction sector. As a research method, PEST is used for the study of local construction trends. At the same time, stakeholders are interviewed using semistructured surveys organized according to the ReSOLVE framework (regenerate, share, optimize, loop, virtualize, and exchange) to identify the barriers and opportunities for circular economy in the construction sector. As an outcome of this study, the most common barriers and opportunities were associated with the economic benefit factor, as this was the main motivation for the stakeholders to save construction materials for reuse or to refuse more eco-friendly technologies. Additionally, policy recommendations for companies involved in the construction ecosystem were provided according to the assessment of found barriers and opportunities in the context of the ReSOLVE framework. This analysis has shown that for most stakeholders of the Kazakhstani construction sector, virtualization is of the highest priority; therefore, opportunities for its development are recommended. Future research could focus on the development of economically feasible solutions for the circular economy in construction with the inclusion of virtualization technologies.
Keywords: Type of access: Open Access; green building; sustainable construction; project delivery; ReSOLVE; PEST; construction and demolition waste; stakeholders’ interview; design for disassembly; BIM